Landscape Arrangement of Cacalan Beach Tourism Area with Natural Building Concept in Sukowidi Village - Wiryasuta, I Ketut Hendra; Ariyanto Sandi, Enes; Galuh Khomari, Mohamad (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
Tourism is one of the sectors that become an economic foundation of the residents of Banyuwangi Regency. Cacalan Beach is one of the natural tourist destinations on the eastern coast of Banyuwangi Regency, precisely in Sukawidi Village. Currently, the management of the Cacalan Beach tourism area is managed by the Tourism Awareness Group (Pokdarwis). In addition to operational management, Pokdarwis also has a role to develop and manage the Cacalan Beach area. The limited concept of planning and funding caused the development of Cacalan Beach not well conceptualized. Therefore, landscape planning is very important to optimize the use of tourist space. The space of the Cacalan Beach tourism area is currently divided into 3 areas, namely the front entrance area where there is a parking lot and guard post, the middle area which is the place for Micro and Small Businesses (UMK), and the inner area which is the main location for Cacalan beach tourism. Through the arrangement of the landscape of the Cacalan Beach area, the utilization of tourist space on Cacalan Beach can be increased. The concept of natural building development has become an icon so that it can increase tourist visits. Community service activities are carried out by conducting mapping surveys, landscape planning with the concept of natural construction, and making 3D mockups. The results of the arrangement of the Cacalan Beach tourism area in the form of 2D and 3D images, as well as 3D mockups that have been made, can be used as a reference for the development of the area. Hence in the future, the development of regional arrangements can be carried out with a focus in accordance with what has been agreed upon and planned.